RESEARCH ON SEAT VERTICAL IMPАСT PULSE ENVELOPE BASED ON OCCUPANT LUMBAR INJURY INDEX - LIN Ce; LI LeiZi; LI QingFeng (Jixie qiangdu)
According to a certain type of aireraft fuselage structure's crashworthiness(occupant survivability envelope) design requirements, a standard 14g vertical impact test of the 'floor-seat-occupant' system which meet the requirements of AC25.562-1B regulations was carried out first. Then, finite element model calibration of the test was carried out based on Ls-Dyna software. After calibration, in order to simulate the vertical drop conditions, several impact pulses with different peaks and widths were designed, calculated and tested on 80° fixture condition, and obtained the seat vertical impact pulse envelope meeting the occupant lumbar injury index, which provide reference for the design of aireraft fuselage structure. In addition, the concept of seat 'force transfer coefficient K' and the hysteretic effect of seat cushion on passenger lumbar load under different impact pulses were proposed based on the injury index of passenger lumbar load.